Elucidating the antimalarial activity of pityriacitrin isolated from Strophanthus hispidus (DC) whole plant extract: A detailed experimental and in-silico investigation - Faloye K.O.; Ambali O.A.; Ogundele S.B.; Tripathi M.K.; Adesida S.A.; Asiyanbola I.D.; Fakola E.G.; Obaidullah A.J.; Alotaibi J.M.; Oguntimehin S.A. (My University, 2025)
Malaria disease has contributed significantly to the increased mortality rate of children and pregnant mothers in Africa. This study isolated chemical compound from the dichloromethane extract of Strophanthus hispidus, evaluated its antimalarial activity in vivo, carried out molecular docking, molecular dynamics simulation and quantum chemical calculations to elucidate its possible mechanism of action in parasitized mice. The dichloromethane extract was subjected to various chromatographic separation methods to afford pityriacitrin. The antimalarial activity of the isolate was evaluated using curative model. Molecular docking and 100 ns Molecular dynamics simulation was performed against plasmepsin II and plasmodium falciparum dihydrofolate reductase-thymidylate synthase and density functional theory calculations were performed using BL3YP at 6–31 G basis set. The results revealed pityriacitrin as a good antimalarial candidate with 71, 75 and 83 % parasite clearance at 5, 10 and 20 mg/kg. The in silico studies revealed pityriacitrin elicited considerably high binding affinity against the selected enzymes. The RMSD, RMSF and contact plots showed that pityriacitrin exhibited stability throughout the 100 ns simulation period. The quantum chemical properties calculated showed that pityriacitrin demonstrated better drug like properties in water compared to other medium. Our findings suggest extensive in vitro investigation into the inhibitory property of pityriacitrin against malaria enzymes. © 2024